Dystocia due to Schistosomus reflexus in a goat - KALITA, D; BHUYAN, D; MUKIT, A; ISLAM, S (The Indian Journal of Animal Reproduction, 2023)
A stillborn male schistosomus reflexus monster in anterior ventral presentation causing dystocia in a goat was delivered by mutation and traction.